Inhibition Activity of Leaves, Flower and Root Extracts of Ruellia tuberosa L on α-Glucosidase Enzymes - Andi Suhendi; Agus Salim Maulana (Journal of Nutraceuticals and Herbal Medicine, 2020)
Previous study stated that the herba of Ruellia tuberosa L has inhibition activity on α-glucosidase enzymes. The leaves, flowers, and roots of Ruellia tuberosa L contain flavonoids but have different activities. This study aims to determine the inhibitory activity by the leaves, flowers and roots of Ruellia tuberosa on the α-glucosidase enzyme. Extraction was performed by maceration method using ethanol 96% as solvent. Inhibition activity was measured based on the formation of a yellow solution of p-nitrophenol compound as a result of the reaction between p-nitrophenyl-α-D-glucopyranoside (as substrate) and α-glucosidase enzyme at a wavelength of 405 nm. The system reaction of inhibition study is divided into two reactions, namely S0 (contains substrates without enzyme) and S1 (contain substrate and enzyme). The results showed that inhibition activities of leaves, flower and root extract were 9.97 ± 4.97 % at 7.8125 µg/mL concentration of extract; 13.98 ± 5.18 % at 7.8125 µg/mL concentration of extract; 99.08 ± 0.12 % at 31.25 µg/mL concentration of extract, respectively. Based on data, the extract of leaves, flowers and roots of Ruellia tuberosa L. has the potential as an inhibitor of the enzyme α-glucosidase.